A Discourse of Professionalism of Advocates in Providing Legal Assistance in Indonesia - Amelia Putri Rizkyta; Mahmod Umar Dhani (Universitas Negeri Semarang, 2023)
The legal profession of advocacy is a noble pursuit entailing significant responsibility, as it transcends the advocate’s personal interests, extending to the welfare of others. Advocates bear the ethical obligation to assist individuals grappling with legal challenges, particularly those who lack the means to navigate complex legal matters independently. This study employs normative legal research methods and adopts a conceptual approach to delve into the intricate facets of advocate professionalism. The core tenet of advocate professionalism lies in providing legal assistance without charge, guided by a conscientious commitment that transcends any form of discrimination. The efficacy of such pro bono assistance becomes a key metric in evaluating an advocate's professional integrity and societal impact. Despite the commendable nature of this endeavor, various obstacles impede its seamless implementation. By assessing the effectiveness of free legal aid, this study seeks to unveil the true extent of an advocate's contribution to society. It explores the challenges and nuances involved in delivering legal assistance without monetary compensation, shedding light on the delicate balance between professional commitment and practical hindrances. Ultimately, this research aims to provide insights that enhance the understanding of advocate professionalism, emphasizing its crucial role in ensuring equitable access to justice for all segments of society.